NURSING CARE FOR ADOLESCENTS IN PRENATAL - Dantas da Silva, Lorena; de Lira Silva, Macerlane; Batista Abrantes, Kaellen; Venâncio Soares Vieira, José; Silva Oliveira, Geane; Caroline de Souza, Anne; Mikaelly Marques de Abrantes, Fávilla; Marques Galvão, Emanoelly; Lademilla Pordeus Fernandes Dantas, Rita (Health and Society, 2024)
The problematization of teenage pregnancy and its care through prenatal care, being multifactorial, permeated by social and cultural prejudices, poses challenging factors for the practice of nurses in Primary Care. Objective: Highlight the role of the nurse in the sensitized reflection of care, to establish bonds and trust, fundamental for the humanization of this process. Methodology: Integrative review of the literature developed with original articles, published between 2018 and 2023, with the theme of teenage pregnancy and nursing care. Results: It was constructed from this study that the concept of sensitized reflection on the care of pregnant adolescents must value their biographies, their values, their fears and desires; characterizing the nurse’s performance free from prejudice and prejudgment, stigma, aggression or discrimination. Final considerations: It is suggested that the role of nurses working in Primary Health Care is to recommend and ensure that care for pregnant adolescent women, a population so fragile and vulnerable, is more welcoming, attentive, warm, harmonious and humanized than their current practices.